Ion homeostasis and coordinated salt tolerance mechanisms in a barley (Hordeum vulgare L.)doubled haploid line - Hongwei Xu; Hui Chen; Nigel G. Halford; RugenXu; Ting He; Bangwei Yang; Longhua Zhou; HuiminGuo; ChenghongLiu (BMC Plant Biology)
Abstract Salinization poses a significant challenge in agriculture. Identifying salt-tolerant plant germplasm resources and understanding their mechanisms of salt tolerance are crucial for breeding new salt-tolerant plant varieties. However, one of the primary obstacles to achieving this goal in crops is the physiological complexity of the salt-tolerance trait. In a previous study, we developed a salt-tolerant barley doubled haploid (DH) line, designated as DH20, through mutagenesis combined with microspore culture, establishing it as an idea model for elucidating the mechanisms of salt tolerance. In this study, ion homeostasis, key osmotic agents, antioxidant enzyme activities and gene expression were compared between Hua30 (the original material used as a control) and DH20. The results indicated that under salt treatment, DH20 exhibited significantly higher shoot fresh and dry weight, relative plant height, shoot K+/Na+ ratio, improved stomatal guard cell function, and better retention of chloroplast ultrastructure compared to Hua30. Notably, the K+ efflux in DH20 was significantly lower while the Na+ and H+ efflux was significantly higher than those in Hua30 under salt stress in mesophyll cells. Furthermore, the activities of ascorbate peroxidase, superoxide dismutase, and peroxidase, along with the levels of proline, betaine, malondialdehyde, and soluble protein, were correlated with ion efflux and played a vital role in the response of DH20 to salt stress. Compared to Hua30, the relative expression levels of the HvSOS1, HvSOS2, HvSOS3, HvHKT1;3, HvNHX1, HvNHX2, and HvNHX3 genes, which showed a strong correlation with Na+, K+, and H+ efflux, exhibited significant differences at 24 h under salt stress in DH20. These findings suggest that ion homeostasis, key osmolytes, antioxidant enzyme activities, and associated gene expression are coordinated in the salt tolerance of DH20, with K+ retention and Na+ and H+ efflux serving as important mechanisms for coping with salt stress. These findings present new opportunities for enhancing salinity tolerance, not only in barley but in other cereals as well, including wheat and rice, by integrating this trait with other traditional mechanisms. Furthermore, MIFE measurements of NaCl-induced ion fluxes from leaf mesophyll provide plant breeders with an efficient method to screen germplasm for salinity stress tolerance in barley and potentially other crops. Clinical trial number: Not applicable.